The analysis of phenomenological experiences based on Giorgi method - Hasanvand, Shirin; Ashktorab, Tahereh; Seyedfatemi, Naemeh; salmani, Naiire (Advances in Nursing & Midwifery, 2016)
Abstract: Unquestionably, data analysis is the most complex and mysterious of all of the phases of a qualitative research, and the one that receives the least thoughtful discussion in the literature. The aim of this review paper that adapted from methodology section of doctoral dissertation was outlines the descriptive phenomenological psychological method of research and explain of data analysis based on Giorgi approach with objective examples to cause further insight and reflection by later researchers who may this choose as most appropriate method to analyze their data. Data analysis based on Giorgi framework follows Husserl tradition. Description and clarification of the phenomenon being studied is cornerstones of this phenomenological method. The stages of analysis method based on Giorgi are: 1) assuming phenomenology attitude, 2) read of interview to attain of Sense of the whole, 3) determination of primary meaning unites, 4) transforming of meaning unites to psychological statements , and 5) synthesize of psychological General or Essential structure of experience based on constituents. Among the analysis approaches of qualitative data, analytical method of Giorgi has been as least preferred method by local researchers. However, the review of literature suggests that many foreign studies have used this approach to analyze data, describing the data analysis with comprehensive details has not been mentioned. Providing more details on the method of data analysis, allowing researchers access to necessary information and will be useful as a guide for future research. therefore, The data analysis procedures are described in detail in the paper and this matter has been resolved. Keywords: Qualitative Researches, Phenomenology, Descriptive phenomenology, Giorgi analytic approach